Penerapan Kain Etnik Bali Pada Busana Pria Dalam Media Belajar Jurnalistik Fashion - Pandansari, Purwosiwi; Purwanti, Rina; Budiyanto, Ari Eko; Kristanti, Kristanti (Jurnal Ilmiah Global Education, 2025)
The research to learn fashion journalism that applies the theme of men's fashion using Balinese endek cloth. Balinese endek cloth is a cultural heritage that should be preserved, men's clothing is displayed in the form of a fashion catalog with various styles of work clothing themes. There are not many fashion journalism learning media for men's fashion by making this research as a means of developing teaching media for students on men's fashion and applying it to suitable photo styles for men's fashion using Balinese endek cloth. The method used in this research is a descriptive qualitative approach to the process of fashion planning and fashion photography of men's fashion based on Balinese ethnic cloth. The results of the study are a catalog that shows that Balinese etink cloth in men's fashion can be a modern men's fashion style without leaving local cultural values and is suitable for use in fashion journalism teaching media, especially men's fashion.